Evaluation of bone marrow mesenchymal stem cells growth in vitro for cartilage tissue engineering - Ahmad Radzi, Muhammad Aa'zamuddin; Jamaludin, Fatin Nabila; Abdul Rahman, Rozlin; Md Nazir, Noorhidayah; Mohamad Sukri, Norhamiza; Mohammad, Mohd Yusof; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Abdul Rahman, Suzanah; Hashi, Abdurezak Abdulahi; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Stem cell has been widely researched during the last decade due to its potential to differentiate into many cell types. This study attempts to compare the growth of bone marrow mesenchymal stem cells (BMMSC) aspirated from rabbits’ iliac crest and femur in two culture media i.e. (1) α-Minimum Essential Medium (α-MEM) and, (2) the mixture of Ham F12 Nutrient Mixture and Dulbecco’s Modified Eagle Medium (FD). Growth kinetics assessment used in this study includes cell viability, total cell yield, growth rate, population doubling time and total number of cell doubling. FD was found to be an appropriate culture medium to promote better BMMSC growth. BMMSC from iliac crest region showed better proliferation potential than the femur region. Hence, it can be inferred from this study that BMMSC harvested from the iliac crest site and cultured in FD medium is better than femur samples in terms of growth profile.